Study on the Effectiveness of Thrombolytic Drugs in Emergency Treatment of Ischemic Stroke: Time and Outcome Analysis - Tarigan, Indra (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Ischemic stroke is one of the leading causes of morbidity and mortality worldwide. Thrombolytic therapy, such as the use of alteplase (tPA), is an effective standard of care when given in a timely manner. However, its effectiveness in clinical practice still varies, especially related to factors such as the time of drug administration and patient clinical outcomes. This study aims to analyze the effectiveness of thrombolytic drugs in ischemic stroke emergencies based on the relationship between the time of drug administration and patient clinical outcomes, using univariate and bivariate analysis. This study used an observational analytical design with a retrospective approach. Data on ischemic stroke patients who received thrombolytic therapy were collected from medical records at the hospital during a certain period. The independent variables included onset-to-needle (OTN) time and door-to-needle (DTN) time, while the dependent variable was clinical outcome based on the National Institutes of Health Stroke Scale (NIHSS) and modified Rankin Scale (mRS). Univariate analysis was used to describe the distribution of patient characteristics and main variables, while bivariate analysis was performed with correlation and logistic regression tests to see the relationship between the time of drug administration and patient outcomes. The results of univariate analysis showed that the majority of patients (70%) received thrombolysis within the OTN time range <3 hours, with an average initial NIHSS value of 12.5 ± 4.3. From the bivariate analysis, a significant relationship was found between DTN time <60 minutes and improvement in NIHSS score after 24 hours (p <0.05). In addition, patients with mRS <2 at 90 days after therapy were more common in the group receiving thrombolytics faster (OTN <3 hours) than those who received slower (p <0.01).